Contribuição para a supressão dos acidentes de trabalho fatais nas etapas da cadeia produtiva de energia elétrica - Silva, Luis Geraldo Gomes da (2017)
This research aims at contributing to the suppression of fatal work accidents in the electricity sector, discussing the problem on three fronts: a) extend the scope of the fatal work accident data banks to the entire electrical energy production chain including services of third-party companies; b) include in the fatal accidents databases information to assess the conditions under which accidents occurred and formulate solutions to avoid them in the future; c) to monitor and quantify, through Bayesian networks, the level of safety culture of the companies in the electricity sector, assuming an inverse correlation between the level of safety culture and the number of fatal accidents in these companies. The electricity sector is usually represented by the stages of generation, transmission and distribution of electricity. However, the electrical sector, considering its entire production chain, is much larger and 15 stages have been identified from primary energy prospecting to the decommissioning of facilities after their useful life. Regarding work accident databases, in Brazil there are three databases covering only the generation, transmission and distribution stages of the electricity sector. It was found that they do not present complete data to trace the root causes of accidents and identify possible solutions to avoid them in the future. For example, between 2009 and 2015, 69 self-employed workers and 380 outsourced workers died in the distribution stage without further details of the conditions under which these accidents occurred. The inclusion of thirdparty companies in the accounting of work-accident statistics can be a factor in improving the working conditions of the entire energy sector. The economic power of leading companies can demand from their partners better behavior in terms of work safety and suppression of fatal accidents. It was proposed a minimum database structure of work accidents in the electric sector with information that allows, among other objectives, the traceability and subsequent correction of accidental events. These items include the accident record number, name, type and area of work of the company, and opinions of the accident work safety monitoring system, including those from the CIPA, occupational physician, union and technical supervisor. Maintaining a level of safety culture in a company is important for the suppression of occupational accidents. A safety culture monitoring model based on Bayesian networks with 15 different variables was developed. These variables range from senior management engagement with work safety to workers training in the use of personal protective equipment. This quantitative model was able to capture differences in the safety culture level of 15 different electricity distribution companies and show a clear inverse correlation with the number of fatal accidents.